Balancing Acts: A Phenomenological Study of Single Mothers Who Are Successful Students in Higher Education - Rosemary Buteau (Adult Education Research Conference, 2007)
This research sought to discover the characteristics of single mother students in higher education who successfully balanced their many responsibilities associated with their roles as mother, employee, family member, friend, and college student. While telling their stories, these women also offered suggestions to administrators and faculty in higher education.